Miscarriage: Emotional burden and social suffering for women in Pakistan. Issue 10 (25th November 2016) - Batool, Syeda Shahida; Azam, Hareem
ABSTRACT: The study aimed to explore the bereavement experiences of women after miscarriage. Ten women who experienced miscarriages of their first child were interviewed. Verbatim interviews were analyzed through the principles of Interpretative Phenomenological Analysis that yielded eight super ordinate themes: shattered planning; physical and emotional pain; reaction to miscarriage; transformed marital relationships; in-laws' support; blame attribution; identity and well-being; and posttraumatic growth. The participants shared the constant psychological and physical pain they felt after miscarriage. The results reveal that cultural awareness is crucial when addressing the healthcare needs of women who undergo similar reproductive losses in different cultures.